Perempuan Tionghoa dalam Sejarah Olahraga Indonesia, 1908-1949: Dari Eksistensi hingga Memperjuangkan Kemerdekaan Indonesia - Shodiq, Pasang Budy All (Lembaran Sejarah, 2024)
This research explores the involvement of Chinese women in the history of sports in Indonesia from the Dutch East Indies period to the Indonesian Revolution. Chinese women, who have been received less attention in the history of Indonesian sports, actually have a role in the process of sports development in Indonesia. Their influence can be seen through how they interpreted sports differently in each era. This research employs historical method to explain women’s involvement in sports history in Indonesia, drawing from sources such as newspapers, photos, and other scholarly materials. The findings are analyzed using the social history approach to comprehend and illustrate the trends in Chinese women’s involvement in the history of sports in Indonesia. This topic introduces a new area in Indonesian historiography and can serve as a fresh point of reference for historians interested in the history of sports and the Chinese community in Indonesia.